2014
DOI: 10.1097/md.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fecal and Mucosa-Associated Microbiota in Chinese Patients With Inflammatory Bowel Disease

Abstract: The intestinal microbiota plays an important role in the pathogenesis of inflammatory bowel disease (IBD), and geographical and genetic backgrounds impact the composition of the intestinal microbiota. However, there is a lack of evidence regarding the overall changes and characteristics of fecal-associated microbiota (FAM) and mucosa-associated microbiota (MAM) in Chinese patients with IBD. We recruited 26 patients with Crohn’s disease (CD), 46 patients with ulcerative colitis (UC), and 21 healthy individuals;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
149
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(166 citation statements)
references
References 54 publications
16
149
1
Order By: Relevance
“…35 We found a significant decrease in the relative abundance of the genus Roseburia in the UC patients, which is consistent with previously reported studies. 15,20,36 The genus Roseburia includes known butyrate producing organisms and butyrate can interact with the intestinal epithelium to produce an antiinflammatory environment 37 and modulate intestinal barrier function. 38 In patients with UC, a decrease in SCFA production is correlated with reductions in Roseburia abundance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 We found a significant decrease in the relative abundance of the genus Roseburia in the UC patients, which is consistent with previously reported studies. 15,20,36 The genus Roseburia includes known butyrate producing organisms and butyrate can interact with the intestinal epithelium to produce an antiinflammatory environment 37 and modulate intestinal barrier function. 38 In patients with UC, a decrease in SCFA production is correlated with reductions in Roseburia abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models revealed that Faecalibacterium prausnitzii has antiinflammatory properties and, in patients with CD, reductions in ileal F. prausnitzii abundance were associated with disease recurrence. 14 In patients with UC, studies have reported either no change 4,10,15 or lower 4,9,[16][17][18] abundance of F. prausnitzii. However, select patients with UC may carry increased amounts of this bacterium in the colonic mucosa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the genus level, only Coprococcus changed (increased) in abundance by more than twofold. The abundance of Coprococcus (a genus including butyrate-producing bacteria) has been found to be decreased in inflammatory bowel disorder (IBD) patients (5). Therefore, the increased abundance of Coprococcus and Lachnospiraceae upon the FMT series may have delivered beneficial effects to the colonic epithelium of the UC patients (recipients).…”
Section: To the Editormentioning
confidence: 99%
“…Although the majority of studies have assessed gut microbial diversity through analysis of faecal samples, their ability to reflect microbial diversity at the mucosal surface is inadequate [2123]. Mucosal biopsies display greater microbial diversity than faecal samples [24] as well as taxonomic and phylogenetic differences [25] and contrasting dominant bacterial populations [22].…”
Section: Introductionmentioning
confidence: 99%